Risks of Influencer Marketing and Their Impact on The Consumer: An Empirical Study in Slovakia - Jakub MICHULEK; Anna KRIZANOVA (Communications of International Proceedings, 2022)
Long before the internet hit our world, influencer marketing was practiced traditionally. Businesses have mostly used social influencers, such as sportsmen, etc., for decades to support goods or services through traditional media. However, the emergence of social networks has fundamentally changed how marketing works today. Influencers on social media have a significant impact on the (digital) lives of millions of people worldwide. Modern influencer marketing depends on social media influencers, or people with a sizable social media following, to increase online interest in goods or services that a company or brand has supported. The aim of this research is to find out the risks of influencer marketing and how they will affect consumer behavior. We used factor analysis to reveal risks that can be used in further research. More than 60% of respondents know the term "influencer marketing". We have identified the biggest risks of influencer marketing, such as cooperation with an influencer with a small number of followers; promoting with an influencer who does not follow the same lifestyle as the brand with which he or she cooperates; etc. Almost 60% of people aged 18–25 would have no problem buying a product promoted by a virtual influencer. From this, it can be concluded that the young people to whom this type of influencer is directed are trustworthy for them. It is therefore possible to consider the virtual influencer as the future of influencer marketing.
Keywords: Influencer marketing. Influencer. Communication. Marketing communication. Social Media